2017
DOI: 10.1371/journal.pone.0184494
|View full text |Cite
|
Sign up to set email alerts
|

High HPgV replication is associated with improved surrogate markers of HIV progression

Abstract: BackgroundHuman Pegivirus (HPgV) may have a beneficial effect on HIV disease progression in co-infected patients; however, the virologic characteristics of this infection are not well defined. In this study, we determined HPgV viremia prevalence in Mexico and provide new insights to understand HPgV infection and HPgV/HIV co-infection.MethodsWe analyzed and quantified 7,890 serum samples for HPgV viremia by One-Step RT-Real-Time PCR, 6,484 from healthy blood donors and 1,406 from HIV-infected patients. Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…Similar to a study in Mexico, we observed two broad groups, low and high, of HPgV-1 viremic individuals, de ned by a cut off value of 600,000 RNA copies/ml. This observation likely re ects the different viral replication states within infected volunteers [22]. We observed similar numbers of high and low viremic individuals, who are infected with HPgV-1 genotype 2.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to a study in Mexico, we observed two broad groups, low and high, of HPgV-1 viremic individuals, de ned by a cut off value of 600,000 RNA copies/ml. This observation likely re ects the different viral replication states within infected volunteers [22]. We observed similar numbers of high and low viremic individuals, who are infected with HPgV-1 genotype 2.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to a study in Mexico, we observed two broad groups, low and high, of HPgV-1 viremic individuals, categorized by a cut off value of 600,000 RNA copies/ml. This observation likely reflects the different viral replication states within infected volunteers [24]. We observed similar numbers of high and low viremic individuals, who are infected with HPgV-1 genotype 2.…”
Section: Discussionsupporting
confidence: 59%
“…Extending this observation, our findings corroborate the hypothesis suggested that HPgV does not exert a protective effect during the acute phase of HIV infection, since the HIV positive individuals in this study were all newly diagnosed. Otherwise, as seen in several other studies, there is a likely beneficial relationship between HPgV and the chronic phase of HIV infection [4,47,52,53].…”
Section: Discussionmentioning
confidence: 74%